Spinal Epidural Hematoma after Thoracolumbar Posterior Fusion Surgery without Decompression for Thoracic Vertebral Fracture - Tsuyoki Minato; Masayuki Miyagi; Wataru Saito; Shintaro Shoji; Toshiyuki Nakazawa; Gen Inoue; Takayuki Imura; Hiroaki Minehara; Terumasa Matsuura; Tadashi Kawamura; Takanori Namba; Naonobu Takahira; et al. (Case Reports in Orthopedics)
We present a rare case of spinal epidural hematoma (SEH) after thoracolumbar posterior fusion without decompression surgery for a thoracic vertebral fracture. A 42-year-old man was hospitalized for a thoracic vertebral fracture caused by being sandwiched against his back on broken concrete block. Computed tomography revealed a T12 dislocation fracture of AO type B2, multiple bilateral rib fractures, and a right hemopneumothorax. Four days after the injury, in order to promote early orthostasis and to improve respiratory status, we performed thoracolumbar posterior fusion surgery without decompression; the patient had back pain but no neurological deficits. Three hours after surgery, he complained of acute pain and severe weakness of his bilateral lower extremities; with allodynia below the level of his umbilicus, postoperative SEH was diagnosed. We performed immediate revision surgery. After removal of the hematoma, his symptoms improved gradually, and he was discharged ambulatory one month after revision surgery. Through experience of this case, we should strongly consider the possibility of preexisting SEH before surgery, even in patients with no neurological deficits. We should also consider perioperative coagulopathy in patients with multiple trauma, as in this case.